(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
Technological and medical development imposes paradigmatic dilemmas: are parents morally obliged to conduct preimplantation genetic diagnosis [hereinafter, PGD] or not, and as a consequence, are they responsible on an individual level to make decisions on behalf of their future children that will ultimately affect the wellbeing of human’s future generations, and finally, is the State compelled to guarantee full access to PGD. The scope of this paper will be focused exclusively on these ethical and legal controversies surrounding the obligation to create healthy offspring relating it with the concept of responsible reproduction, placing them in the global international arena.